Refractive status and optical components in premature infants with and without retinopathy of prematurity: A 4- to 5-year cohort study - Xie, Xuanxuan; Wang, Yang; Zhao, Rulian; Yang, Jing; Zhu, Xiaohui; Ouyang, Lijuan; Liu, Ming; Chen, Xinke; Ke, Ning; Li, Yong; Pi, Lianhong (Frontiers in Pediatrics, 2022)
This study aimed to investigate the characteristics of refractive parameters in premature infants and children with mild retinopathy of prematurity (ROP) at the age of 3-8 years. Premature infants who underwent ocular fundus oculi screening were included and divided into ROP group and non-ROP group. The term infants served as controls. The results of annual ocular examination were collected. The refractive status, optical components, and developmental trends were compared among three groups. Results showed that the incidence of myopia and astigmia was the highest in ROP group, followed by the non-ROP group, and lowest in control group. The incidence of myopia increased, but that of hyperopia decreased over age in three groups (P<0.05). In ROP group, the corneal refractive power was the largest, the lens were the thickest and the ocular axis was shortest; in control group, the corneal refractive power was smallest, the lens were the thinnest, and the ocular axis was the longest. The corneal refractive power was relatively stable at the age of 3-8 years in three groups. The lens thickness became thinner in control group (P<0.001). In conclusions, premature infants with or without ROP are more likely to develop myopia and astigmia as compared to full-term infants. Premature delivery is a main cause of high incidence of myopia, and the high incidence of astigmia is mainly related to ROP. Besides the influence of ocular axial growth, the thicker lens are the main cause of high incidence of myopia in premature infants with or without ROP.